"Do unto others what you want … ": Reciprocity and childcare in the Kumasi metropolis of Ghana. Issue 5 (3rd September 2019) - Owusu, Samuel Asiedu
Abstract : This exploratory study aimed to assess reciprocity qualities in childcare and likely influences on child health outcomes. Informants were 83 child caregivers from the Kumasi metropolis of Ghana. Of these, 56 individual maternal ( n  = 28) and non-maternal child caregivers ( n  = 28) completed in-depth individual interviews. Another 23 participated completed focus group discussions, while four key informants shared their expert views on the subject-matter. All the participants responded to open-ended questions on positive and negative reciprocity in childcare. Thematic analysis of the data revealed dyads of positive reciprocal maternal and household non-maternal supports for child well-being. Conversely, negative reciprocal relational outcomes between maternal and non-maternal caregivers were detrimental to children, placing them at risk for various forms of maltreatment. Future studies should consider the conditions in which positive reciprocity is likely to thrive with a view to promoting sustainable child caregiving in Ghanaian societies.